A randomized trial of Lactobacillus rhamnosus IDCC 3201 tyndallizate (RHT3201) for treating atopic dermatitis. Issue 7 (31st May 2020) - Jeong, Kyunguk; Kim, Mincheol; Jeon, Se Ah; Kim, Young‐Hoo; Lee, Sooyoung
Abstract: Background: Probiotic therapies, mainly live bacteria, have been proven to be effective in treating atopic dermatitis (AD) with some controversies. Killed probiotics or postbiotics would have immunomodulatory effect in allergic diseases including AD. This study was performed to evaluate the therapeutic effect and safety of tyndallized Lactobacillus rhamnosus (IDCC 3201, isolated from the feces of a Korean breastfed infant, repeated heat‐treated and incubated, RHT3201) in children with AD. Methods: In a randomized, double‐blind, placebo‐controlled study, RHT3201 at a dose of 1.0 × 10 10  CPU/d or placebo was given in children (aged 1‐12 years) with moderate AD for 12 weeks. SCORing of AD (SCORAD) scores, allergic inflammatory markers, and safety parameters were evaluated. Results: For evaluating the therapeutic effects of RHT3201, 33 subjects in each group were analyzed. The change of SCORAD total score at 12 weeks (primary outcome) from baseline was significantly greater in the RHT3201 group (−13.89 ± 10.05) compared to the control group (−8.37 ± 9.95). Levels of eosinophil cationic protein (ECP) and interleukin (IL)‐31 showed tendency to decrease in the RHT3201 group and significant decreases in subgroup analysis in AD for ≥50 months. For safety analysis, a total of 100 subjects (50 in the treated group and 50 in the control group) were evaluated, and there were no significant differences in safety parameters between two groups. Conclusion: In children with moderate AD, oral administration of RHT3201 showed the therapeutic effect on AD, the effects in part correlated with decrement of ECP and IL‐31, and the effect was more remarkable in subgroup analysis.